Pengaruh Perputaran Persediaan, Laba Produksi, dan Biaya Operasional terhadap Laba Bersih (Pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Riani Sukma Wijaya (JURNAL PUNDI, 2022)
This study aims to determine the effect of inventory turnover, production costs and operational costs on net income (in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period). This type of research is a quantitative study with a population of 53 companies in various industrial sectors listed on the Indonesia Stock Exchange in the 2015-2019 period. The data used is in the form of annual financial reports for various industrial sectors which were sampled in the study with a period of five years. The sample of this study was determined using a purposive sampling method in order to obtain 20 manufacturing companies in various industries. The type of data used is secondary data obtained from the respective company's wabsite and www.idx.co.id. The analysis method used is descriptive statistics, classical assumption test, multiple linear regression and hypothesis testing using SPSS version 25. The results of the research partially show that inventory turnover has no effect on net income, production costs have a significant effect on net income and operating costs have no effect on net income. The results of the research simultaneously show that inventory turnover, production costs and operating costs have an effect on net income.